Experimental and Numerical Study on the Comparative Flexural Behavior of Geopolymer Concrete Beams Based on Metakaolin and Fly Ash - Purba, Luki Hariando; Hutagalung, Bartholomeus; Perangin-angin, Siwan (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
This study investigates the flexural behavior of normal concrete (BN), fly ash-based geopolymer concrete (BGPF), and metakaolin-based geopolymer concrete (BGPM) through both experimental testing and Finite Element Method (FEM) analysis. The objective is to compare the mechanical properties, load-bearing capacities, and post-yield behavior of these materials. The experimental results indicate that normal concrete beams (BN) exhibited the highest performance in terms of cracking load, yield load, and maximum load, demonstrating both high strength and ductility. The fly ash-based geopolymer concrete (BGPF) showed lower strength than BN but still performed significantly better than the metakaolin-based geopolymer concrete (BGPM). BGPF displayed a more brittle behavior post-yield, with a sharp reduction in load-bearing capacity, making it less suitable for structures requiring significant post-yield deformation. The BGPM beams demonstrated the lowest mechanical performance, primarily due to insufficient curing. The metakaolin material was only heated to 200°C due to laboratory limitations, far below the optimal temperature of 700-800°C necessary for full geopolymerization. As a result, the BGPM beams remained brittle and exhibited minimal load-bearing capacity compared to BN and BGPF. FEM analysis, while providing useful insights into the flexural trends, tended to overestimate the load-bearing capacities and deflections across all beam types compared to experimental results. In conclusion, geopolymer concrete, particularly fly ash-based, shows promise as an alternative to traditional concrete, though its mechanical properties, especially ductility and post-yield behavior, require further optimization. The study highlights the importance of proper curing processes, especially for metakaolin-based geopolymer concrete, to fully realize its potential as a sustainable building material. Future research should focus on refining these processes to enhance the strength and flexibility of geopolymer concrete.